Agen Perubahan di SMKS Penerbangan Angkasa Nasional Kota Padang - Khasanah, Havizatul; Rifma, Rifma (Universitas Negeri Malang, 2024)
Abstract : A change agent is a person who is able to bring about change within his/her institution. Change agents are usually people who are confident and have an optimistic attitude, so that with that attitude a change agent can invite other members or colleagues to be able to change even he is able to bring change in his institution. In schools, change agents can be principals, teachers, students or parents. In general, the change agent in the school is the principal as a leader who is able to invite members to change because he has a high position in the school. The research method used in writing this article is a qualitative method with an observation approach and interview sources. The research was conducted to find out the agents of change that exist in SMKS Penerbangan Angkasa Nasional Padang city and how the role of these agents of change. It can be seen that the agent of change at SMKS Penerbangan Angkasa Nasional is the principal as the school leader and the changes made by the school there are 2 types of changes, namely physical and non-physical changes, the changes made in this school did not get rejection from the school community because it was considered that the changes had a good impact on the development of the school.abstrak : Agen perubahan adalah orang yang mampu membawa perubahan didalam lembaganya. Agen perubahan biasanya orang yang percaya diri dan memiliki sikap yang optimis, sehingga dengan sikapnya itu seorang agen perubahan dapat mengajak anggota lain atau rekannya untuk dapat berubah bahkan ia mampu membawa perubahan dalam lembaganya. Di sekolah agen perubahan bisa jadi kepala sekolah, guru, siswa maupun orang tua siswa. Pada umumnya agen perubahan di sekolah itu adalah kepala sekolah sebaagi pemimpin yang mampu mengaja anggota untuk dapat berubah karena ia memiliki jabatan yang tinggi di sekolah. Metode penelitian yang digunakan dalam penulisan arikel ini adalah metode kualitatif dnegan pendekatan observasi dan interview narasumber. Penelitian dilakukan untuk mengetahui agen perubahan yang ada di SMKS Penerbangan Angkasa Nasional kota Padang dan bagaimana peranan agen perubahan tersebut. Dapat diketahui bahwa agen perubahan di SMKS Penerbangan Angkasa Nasional adalah kepala sekolah selaku pemimpin sekolah dan perubahan yang dilakukan sekolah ada 2 jenis perubahan yaitu perubahan fisik dan non fisik, perubahan yang dilakukan di sekolah ini tidak mendapatkan penolakan dari warga sekolah karena dianggap perubahan berdampak baik terhadap perkembangan sekolah.